Science News Agencies in SciComm: an exploratory index for evaluating and enhancing public interest in mass-distributed press releases (SciELO Preprints, 2024)
Scientific press releases are reaching the public directly through press reproduction or institutional dissemination. Science News Agencies (SNAs) mediate this process, distributing texts to thousands of journalists while also "leaking" them on their websites and social media. This comparative case study examines four SNAs — BORI, SMC UK, AlphaGalileo, and EurekAlert! — regarding their role in circulating public scientific information. Through literature review and principles such as openness and inclusion in science, we converted scholars' concerns into a preliminary index potentially capable of assessing SNAs' public suitability. The SNAPI (Science News Agencies Public Index) suggests a shift from purely public relations content towards serving the public interest, highlighting areas needing attention in SNAs' social function, to be refined in future research. Clear guidelines, links to open scientific articles, and explicit notices on press releases’ purposes are simple yet effective ways to address issues concerning science public relations' pervasiveness in the public sphere.